Lanskap Ritual Gua Buatan Masa Klasik Hindu-Buddha di Kediri dan Tulungagung - Aditya Revianur (Jambura History and Culture Journal, 2026)
Landscapes of Ancient East Javanese Hindu-Buddhist religious sites were not built anywhere, their position determined by people perspective in the 11th to 15th century. The ancient East Javanese religious sites were built on the slopes of hills. This paper reveals the main trait of landscape archaeology approach in archaeology to the rock-cut architecture, i.e. cave temples and hermitages in the ancient Javanese period (11th up to 15th centuries). Landscape Archaeology provides valuable clues about how ancient Javanese people saw the landscape around them, and how it was developed and created. It confirms the importance of space based on Hindu-Buddhist cosmological concept which determined the ritual landscape. This cosmological space also reveals the division of slopes based on the level of the places according to Triloka concept which explains lower world (Bhurloka), middle world (Bhuvarloka), and upper world (Svarloka). This thesis also offers a reflection on the structure of the religious places and its relations with conceptualized space, showing the influence of Hindu-Indian thought, as well as its limits.